Mean platelet volume in patients with prolactinoma - Tam,Abbas Ali (2016)
ABSTRACT Objective Prolactin is a multifunctional pituitary hormone. The effect of prolactin on platelet activation is not well understood. Prolactinomas are the most common type of pituitary adenomas, and they are medically responsive to dopamine agonists. Mean platelet volume (MPV) is a marker of platelet function and activation. The aim of this study was to evaluate MPV values before and 6 months of cabergoline treatment when normoprolactinemia was achieved. Subjects and methods A total of 101 newly diagnosed prolactinoma patients and 102 healthy control subjects were included in the study. Patients with hematological disorders that affect MPV and those on medications were excluded. Prolactin, platelet count and MPV levels were recorded before and 6 months after the initiation of cabergoline treatment (0.5 to 1 mg, two times a week). Results There was no significant difference in platelet count and MPV before and after 6 months of treatment with cabergoline in patients with prolactinoma compared with the control group (p > 0.05). Conclusion Our results showed that MPV, a marker of platelet function, was unchanged in patients with prolactinoma.